Corrosion-resistant coating on AZ91D magnesium alloy based on one-step hydrothermal. (19th May 2023) - Jiang, Min; Li, Shimeng; Zhu, Jiyuan
ABSTRACT: Magnesium alloys are widely used due to their excellent properties, but their corrosion resistance is limited by their high chemical activity. This paper proposes a one-step hydrothermal method with a relatively short reaction time and simple experimental steps for synthesising magnesium alloy coatings with good corrosion protection properties. The surface morphology, chemical composition and corrosion resistance of the in situ generated coatings were investigated using measurements such as field emission scanning electron microscopy (SEM), adhesion cross-cut tape (ACCT) test, X-ray diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), electrochemistry and immersion test, the results revealed that the corrosion current density (Icorr ) of the coatings decreased by approximately four orders of magnitude and had good corrosion resistance.